Computational insight into the mechanism and origins of high selectivities in the acylation of polyamines with 5-benzoyl-5-phenyl-1, 5-dihydro-4H-pyrazol-4-one. Issue 1 (7th December 2018) - Zhang, Yan; Yang, Yongsheng; Yang, Junxia; Yang, Lian; Xue, Ying
Abstract : Density functional theory was used to study the mechanism as well as the rate- and site-selectivities of the acylation reaction. Abstract : Amide bonds have gained much attention from numerous scientists and acyl transfer is a good way to form amide bonds. The acylation mechanism of polyamines and their high selectivity in dichloromethane were investigated by the use of the density functional theory (DFT), M06-2X/6-311+G (d, p)//M06-2X/6-31G (d, p) method combined with the solvation SMD model. The calculated results suggest that the reaction process involved two steps: an acylation step and a proton-transfer step, with the former being the rate-limiting step. Meanwhile, with the substituent group effects of amines and 5-acyl-5-phenyl-1, 5-dihydro-4 H -pyrazol-4-one (BCPP) on the acylation step, different substituent groups of amines have little influence on the kinetic properties of the acylation step, and the para -substituent groups of the phenyl group in BCPP lead to a linear relationship according to the electronegativity of the substituents. Furthermore, regarding the rate-selectivity of amines, the rate-selectivity of primary amines is higher than that of secondary amines, and polyamines very easily take part in acylation owing to the intramolecular hydrogen bond interaction. Moreover, it is harder for the amine group which has an α-position substituent group in polyamines to take part in an acylation reaction compared to the one without an α-position substituent group. The site-selectivity of the acylation process in polyamines is determined by steric hindrance. What's more, the auxiliary analysis of the distortion/interaction analysis and the frontier molecular orbital (FMO) analysis is used to investigate the origins of the rate- and site-selectivities.